2002
DOI: 10.1046/j.1432-1033.2002.03321.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of Francisella tularensis lipopolysaccharide

Abstract: The structure of the lipid A and core region of the lipopolysaccharide (LPS) from Francisella tularensis (ATCC 29684) was analysed using NMR, mass spectrometry and chemical methods. The LPS contains a β‐GlcN‐(1–6)‐GlcN lipid A backbone, but has a number of unusual structural features; it apparently has no substituent at O‐1 of the reducing end GlcN residue in the lipid part in the major part of the population, no substituents at O‐3 and O‐4 of β‐GlcN, and no substituent at O‐4 of the Kdo residue. The largest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
208
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(235 citation statements)
references
References 15 publications
(16 reference statements)
24
208
2
1
Order By: Relevance
“…Compositional analysis by GLC-MS of both core oligosaccharide fractions resulted in identical sugar residues being present in comparable proportions. As expected, the core oligosaccharide fraction of the mutant did not contain contaminating amylopectin (21) and sugars from the O-chain (9). Thus, the Y1C12 mutant was found to be representative for further structural analysis of the complete rough-type C. canimorsus LPS (3).…”
Section: Preparation and Purification Of 1 After Acid Hydrolysissupporting
confidence: 56%
“…Compositional analysis by GLC-MS of both core oligosaccharide fractions resulted in identical sugar residues being present in comparable proportions. As expected, the core oligosaccharide fraction of the mutant did not contain contaminating amylopectin (21) and sugars from the O-chain (9). Thus, the Y1C12 mutant was found to be representative for further structural analysis of the complete rough-type C. canimorsus LPS (3).…”
Section: Preparation and Purification Of 1 After Acid Hydrolysissupporting
confidence: 56%
“…However, the O-antigenspecific glycose N-acetyl quinovosamine (QuiNAc) was not detected in WbtI G191V LPS, confirming that the O antigen was not present in the mutant. The presence of a complete core structure (Vinogradov et al, 2002) in WbtI G191V , but no O antigen, was confirmed by MALDI-MS ( Fig. 2; details in the legend).…”
Section: Physical and Chemical Characterization Of Lpsmentioning
confidence: 80%
“…Most of the work on F. tularensis surface components has focused on the LPS. The LPS of F. tularensis types A and B is unusual in that the O antigen consists entirely of dideoxyglycoses, the core oligosaccharide contains mannose in place of heptose (Vinogradov et al, 2002(Vinogradov et al, , 1991, and lipid A of the live vaccine strain (LVS) is tetraacylated and lacks phosphate (Vinogradov et al, 2002), while lipid A from a virulent type B isolate also contains a phosphatelinked galactosamine (Phillips et al, 2004). Furthermore, the LPS does not signal through TLR4, is not an agonist for TLR4, and does not induce an inflammatory response Cole et al, 2006;Hajjar et al, 2006), which is probably due to the atypical structure of lipid A.…”
Section: Introductionmentioning
confidence: 99%
“…The lipopolysaccharide (LPS) of F. tularensis possesses an atypical lipid A moiety and core structure [15]. Mice deficient in Toll-like receptor (TLR) 4, which binds LPS, do not gain increased resistance to F. tularensis, succumbing to disease as rapidly as do wild-type mice [16].…”
Section: Introductionmentioning
confidence: 99%